2021
DOI: 10.1038/s41598-021-03116-y
|View full text |Cite
|
Sign up to set email alerts
|

Low bend loss femtosecond laser written waveguides exploiting integrated microcrack

Abstract: We introduce the fabrication and use of microcracks embedded in glass as an optical element for manipulating light propagation, in particular for enhancing waveguide performance in silica integrated optics. By using a femtosecond laser to induce a strong asymmetric stress pattern in silica, uniform cracks with set dimensions can be created within the substrate and propagated along a fixed path. The smoothness of the resulting cleave interface and large index contrast can be exploited to enhance waveguide modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Single-mode operation has been optimized for a wavelength of 940 nm, achieving propagation losses down to 0.14 dB/cm and negligible bending losses at curvature radii as low as R = 15 mm. This value shows an improvement of a factor of 2 or higher with respect to the one employed in previous laser-written UPPs [15,16], and it is in line with the state of the art for the FLM platform [25], where advanced techniques for the reduction in bending losses were introduced.…”
Section: Fabrication Improvements 21 Compact Mach-zehnder Interferome...supporting
confidence: 84%
“…Single-mode operation has been optimized for a wavelength of 940 nm, achieving propagation losses down to 0.14 dB/cm and negligible bending losses at curvature radii as low as R = 15 mm. This value shows an improvement of a factor of 2 or higher with respect to the one employed in previous laser-written UPPs [15,16], and it is in line with the state of the art for the FLM platform [25], where advanced techniques for the reduction in bending losses were introduced.…”
Section: Fabrication Improvements 21 Compact Mach-zehnder Interferome...supporting
confidence: 84%
“…The femtosecond laser writing system used to inscribe the waveguides uses 515 nm 200 fs pulses generated from the second harmonic of a 200 kHz 1030 nm Yb:KGW laser pump (PHAROS, Light Conversion Ltd.), see Lee et al 5 for further details. The beam is reflected by a dichroic mirror onto the objective lens (x25 0.4NA PLAN, Leitz Wetzlar) which focuses the light to the sample.…”
Section: Laser Writing Techniquementioning
confidence: 99%
“…The bending radius can roughly be estimated as 3 cm which should be sufficient to suppress bending loss 5 and Fresnel reflection losses can be estimated as 0.36 dB. 10 Overall, it has been shown that waveguides written at or near the surface with estimated ∆n ≈ 3 × 10 −3 perform comparatively with bulk waveguides with α z > 0.6 dB cm −1 .…”
Section: Waveguide Propagation Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that waveguides can be fabricated in a large number of transparent dielectric materials, such as fused silica glass, phosphate glass, lithium niobate (LiNbO 3 ) crystal, and YAG crystal, has been confirmed. Based on these advantages, various femtosecond laser inscribed photonic devices with passive and active functions, including waveguide coupler, waveguide laser, waveguide amplifier, etc., have been successfully realized.…”
Section: Introductionmentioning
confidence: 99%